Multiplier and Innovation effect of the Engineering & Tooling sector in Portugal - Azevedo, N. (2012)
Goals: Measure the “perceptible value” of the Engineering & Tooling sector, not just in terms of annual/monthly revenue flows or profit. Measure the size of the sector in Portugal as a share of the national economy, taking into account its multiplier effect. Model the R&D effect in the sector, given that innovation is intrinsically embedded in the sector’s products and assets, rather than being conducted formally by specialised R&D units